Court Decision Regarding Environmental Compensation Costs: Application In Environmental Restoration - Rizqya Nafila Putri; Dadang Epi Sukarsa; Imamulhadi Imamulhadi (Pelopor Publikasi Akademika, 2024)
Law Number 32 of 2009 concerning Environmental Protection and Management regulates the government has the right to file claims for compensation and certain actions. Minister of the Environment Regulation Number 7 of 2014 concerning Compensation for Environmental Pollution and/ or Damage regulates that environmental compensation costs that have been paid are entered into the Treasury Fund as Non-Tax State Revenue (PNBP). This research identifies the mechanism for using environmental compensation costs, the implementation of Court Decitions containing environmental compensation before Supreme Court Regulation Number 1 of 2023 concerning Guidelines for Adjudicating Environmental Cases, and how this can be a solution to the problem of environmental compensation costs in Indonesia. This research applies a normative juridical approach method using several approaches. The research results show that the environmental compensation costs that have been paid are included in the PNBP, making it difficult to disburse these funds because the long process and the absence of a recovery plan means that the compensation costs charged to the defendant do not have a detailed calculation basis. Supreme Court Regulation Number 1 of 2023 regulates environmental compensation costs are managed in the court clerk's account and lawsuits are required to include a recovery plan.